Enhancing Regional Economy through the Development of a Coconut Sugar-Based Industry in Indragiri Hilir Regency, Indonesia - Desrial, Ahmad; Syaukat, Yusman; Sarma, Ma'mun (Agro Bali : Agricultural Journal, 2025)
The coconut sugar industry in Indragiri Hilir Regency shows good potential due to the high demand for coconut sugar products. However, this potential has not been optimally utilized and there is still low interest from farmers to be involved in this industry, even though the availability of raw materials is very abundant. This study aims to analyze the added value of coconut sugar production between tenant farmers and owner farmers using the Hayami method and formulate development strategies for the coconut sugar industry to improve the regional economy through SWOT and QSPM analysis. This research plays an important role in encouraging the development of the coconut sugar industry as a coconut-derived product that can increase community income and local economic growth. Increase community income and local economic growth.   Data collection methods used include surveys, in-depth interviews, focus group discussions, and literature studies. The results show that with a scheme of 50 coconut trees, each liter of coconut sap generates an added value of IDR 2,794 (71.93%) in the leased coconut system and IDR 3,318 (85.44%) in the owned coconut system. Average monthly production is 462.69 kg, requiring 2,382.69 liters of nira, with profits reaching Rp 2,046 per kg (leased) and Rp 2,571 per kg (owned). The development of the coconut sugar industry is in the “Grow and Build” phase, and although it has high growth potential, there are still several challenges to be faced, including limitations in distribution, infrastructure, and capital. The findings of this study can be applied in local government policies through the preparation of coconut product regulations, integration of the One Village One Product (OVOP) concept in village programs, facilitation of business groups and training by relevant agencies, support for product diversification (liquid sugar and ant sugar) through MSMEs, and promotion of local product branding to increase competitiveness in national and export markets.